Application of structural adhesives
By developing a printable structural adhesive composition containing an epoxy resin, an epoxy curing agent and a toughening agent, the problem of insufficient bonding and sealing performance in the prior art is solved, and rapid and precise bonding and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202380061492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-19
- Filing Date
- 2023-08-08
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to seal metal joints while providing sufficient bonding and provide corrosion resistance, especially in bonding applications with large area and complex structures, where the application speed and accuracy of conventional adhesives are insufficient.
A printable structural adhesive composition is developed, which comprises at least one epoxy resin, at least one epoxy curing agent and at least one toughening agent with a low viscosity (less than 100 Pa·s at 65°C), making it useful for rapid and precise printing application.
It achieves rapid and precise application of adhesive while providing high toughness and good sealing properties, suitable for bonding applications in large areas and complex structures, and provides corrosion resistance.
Smart Images

Figure BDA0005281627200000071 
Figure BDA0005281627200000221 
Figure BDA0005281627200000222
Abstract
Description
Technical Field
[0001] The present disclosure relates to a printable structural adhesive composition for bonding metal parts. In addition, the present disclosure relates to a method for applying the printable structural adhesive composition. The present disclosure also relates to specific uses of the printable structural adhesive composition for bonding and / or sealing. Background Art
[0002] Metal bonding in vehicles can be formed by using adhesives. For example, adhesives can be used to bond metal panels such as vehicle roof panels to the supporting structure or chassis of the vehicle. In addition, adhesives can be used to bond two metal panels of a vehicle closure panel. Vehicle closure panels generally include an assembly of an outer metal panel and an inner metal panel, whereby an edge of the outer panel is folded onto the edge of the inner panel to form an edge-wrapped structure. Typically, an adhesive is provided between the inner and outer panels to bond the panels together. In addition, it is generally necessary to apply a sealant at the joint of the metal panels to provide sufficient corrosion resistance. For example, US 6,000,118 discloses the use of a flowable sealant bead between the facing surfaces of two panels, and a film of an uncured lacquer-like resin between the flange on the outer panel and the exposed surface of the inner panel. The paint film is cured to a solid, impermeable state by performing a baking operation on the complete door panel. US 6,368,008 discloses the use of an adhesive for fixing two metal panels together. The edge of the joint is also sealed by a metal coating. WO 2009 / 071269 discloses an expandable paste epoxy resin adhesive as a sealant for hemming flanges.Another hem construction is disclosed in US 6,528,176.
[0003] Further efforts have been made to develop adhesive compositions, whereby adhesives can be used to join two metal panels (particularly the outer and inner panels of vehicle closure panels) without the need for additional materials to seal the joint. Therefore, it is desirable to develop an adhesive system that also seals the joint and provides corrosion resistance while providing sufficient bonding. A partial solution has been described in, for example, WO 2007 / 014039, which discloses a heat-expandable and curable epoxy precursor of a foaming film toughened by an expanded thermosetting film, the foaming film comprising a mixture of a solid epoxy resin and a liquid epoxy resin, and claims to provide both favorable energy absorption performance and gap filling performance when solidified. Another partial solution has been described in WO 2011 / 141148, which describes a heat-activated structural adhesive that is solid and dry to the touch at ambient temperature, which can be activated to produce adhesive properties at high temperatures, and can be molded without solidification.
[0004] In addition, it is known that the structural adhesive used in automobile manufacturing is usually applied to the substrate in a bead shape. Modern dispensing equipment utilizes robots and pumping equipment to quickly apply adhesive to substrate components (made of metal, or composite materials, plastics and other materials), and then these components are joined, and the adhesive is subsequently cured at elevated temperatures. However, various other designs (such as flat designs, such as cooling plates used in EV battery cooling systems (such as heat exchangers)) with larger and more complex bonding areas will still require long cycle times. This is because structural adhesives must be applied by robots, where dispensing nozzles are moved to all areas where high-viscosity adhesives must be applied. The higher the volume (length of the bonding line) of adhesive, the longer the time spent to complete the cycle.
[0005] On the other hand, seals are needed in many applications. Since the seals of window glass putties were first used to seal window glass in its frame, there have been tremendous advances in the performance and manner of applying sealants (sometimes also called gaskets). In many industries, seals are needed to manage liquids, gases or grease during operation. In areas where larger volumes of sealing materials need to be applied in rapid sequence, materials and methods suitable for rapid process application are desirable.
[0006] Such an area is a fuel cell stack composed of 300 to 400 single fuel cells stacked on each top. A seal between the anode and cathode of a single cell is required to manage fluid during the operation of the fuel cell stack. Therefore, each fuel cell requires 2 seals. For a fuel cell stack composed of 400 fuel cells, 800 seals are required. Generally, it is desirable to use a composition that provides both adhesive bonding bonding performance and sealing performance, or to bond various components together to provide a sealed composition. Therefore, there is an expectation of providing a good adhesive bonding and sealed adhesive composition. In addition, there is an expectation that the adhesive composition can be applied quickly and accurately by a fast automated device. Finally, there is an expectation of a method for applying these adhesive compositions quickly and accurately to a large area and / or a small pattern or structure that is precisely defined.
[0007] Furthermore, there is a need in industry, particularly in the automotive industry, for adhesive formulations and methods and adhesive compositions for bonding parts which allow for precise, economical and safe bonding of metal panels such as dissimilar metal panels during assembly and manufacturing operations such as body-in-white processes. Summary of the invention
[0008] The present disclosure provides a printable structural adhesive composition, the printable structural adhesive composition comprising:
[0009] (a) at least one first epoxy resin;
[0010] (b) at least one epoxy curing agent;
[0011] (c) at least one toughening agent;
[0012] The printable structural adhesive composition exhibits a viscosity of less than 100 Pa×s at 65° C. according to DIN 54458.
[0013] Furthermore, the present disclosure provides a method for applying an adhesive to a substrate, the method comprising the steps of:
[0014] (i) providing a printable structural composition according to any one of the preceding claims;
[0015] (ii) printing the printable structural adhesive composition onto a first substrate;
[0016] (iii) optionally, repeating step (ii);
[0017] (iv) optionally, placing a second substrate on top of the structural adhesive composition on the first substrate;
[0018] (v) performing a curing step to cure the printable structural adhesive composition.
[0019] Finally, the present disclosure provides the use of the printable structural adhesive composition as described herein for joining and / or sealing in industrial manufacturing operations. In one embodiment, the present disclosure provides the use of the printable structural adhesive composition as described herein for repairing holes in electrophoretically coated automobile bodies or parts thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The holes in the car's electrophoretic painted door panels are depicted;
[0021] Figure 2 depicts a perspective view of an adhesive disposed on a patch and an adhesive disposed on a substrate including an aperture;
[0022] Figure 3 A schematic diagram of electrophoretic coating of a car body is depicted;
[0023] Figure 4 A tool for applying force to a patch adhesively bonded to a substrate including a hole, covering the hole, is depicted.
[0024] FIG. 5A to FIG. 8 A method of patching a hole using received data is described. DETAILED DESCRIPTION
[0025] Before explaining any embodiment of the present disclosure in detail, it should be understood that the application of the present disclosure is not limited to the details of the construction and component arrangement given in the following description. The present invention can have other embodiments and can be practiced or implemented in various ways. As used herein, the terms "one", "a kind of" and "said" are used interchangeably and mean one or more; and "and / or" is used to indicate that one or two described situations may occur, such as A and / or B including (A and B) and (A or B). Moreover, in this article, the range expressed by the endpoint includes all numbers contained in the range (for example, 1 to 10 includes 1.4, 1.9, 2.33, 5.75, 9.98, etc.). Moreover, in this article, the expression "at least one" includes all numbers greater than one (for example, at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.). Moreover, it should be understood that the wording and terms used herein are for illustrative purposes and should not be regarded as limiting. In contrast to the use of "consisting of," which is intended to be limiting, the use of "including," "containing," "comprising," or "having," and variations thereof, is intended to be non-limiting and encompass the items listed thereafter as well as additional items. However, it should be noted that the use of "comprising" herein also encompasses the term "consisting of," i.e., the present disclosure itself does not exclude the use of "consisting of" in the sense of "consisting only of."
[0026] Unless otherwise indicated, the amount of the ingredients of the composition can be indicated in weight % (or "% wt" or "wt.-%). Unless otherwise indicated, the amount of all ingredients gives 100 weight%. If the amount of the ingredient is indicated in mole %, the total amount of all ingredients gives 100 mole % unless otherwise indicated.
[0027] In the context of the present disclosure, the terms "room temperature" and "ambient temperature" are used interchangeably and refer to a temperature of 23°C (±2°C) under ambient pressure conditions of about 101 kPa.
[0028] Unless explicitly stated otherwise, all embodiments and optional features of the present disclosure can be freely combined.
[0029] In one aspect, the present disclosure provides a printable structural adhesive composition comprising
[0030] (a) at least one first epoxy resin;
[0031] (b) at least one epoxy curing agent;
[0032] (c) at least one toughening agent;
[0033] The printable structural adhesive composition exhibits a viscosity of less than 100 Pa×s at 65° C. according to DIN 54458.
[0034] The structural adhesive composition described herein exhibits a viscosity of less than 100 Pa×s at 65° C. according to DIN 54458. This means that the structural adhesive composition is a printable adhesive composition, which produces the advantage that the adhesive composition can be applied by printing, particularly by fast automatic equipment or robotic equipment. In addition, substrates of larger areas can be covered by the adhesive composition described herein, and / or small and / or complex structures or patterns can be accurately formed. This can also be advantageously performed by fast automatic equipment or robotic equipment. In combination with components (a), (b) and (c), strong adhesive bonding between substrates exhibiting good mechanical properties can be achieved. In particular, the printable structural adhesive composition according to the present disclosure can provide high toughness, which is highly desirable for a variety of applications in industry, particularly in the automotive industry. Moreover, this strong bonding can also exhibit good sealing properties for a variety of fluids that are often encountered, handled or used in industry.
[0035] In this regard, it is preferred that the printable structural adhesive composition exhibits a viscosity of less than 80 Pa×s, preferably less than 60 Pa×s, more preferably less than 40 Pa×s at 65°C according to DIN 54458. Reducing the viscosity of the adhesive composition according to the present disclosure has the advantage of improving printing performance. This may be particularly true for printing smaller or finer structures or patterns, or generally for printing larger areas. It is further preferred that the printable structural adhesive composition exhibits a viscosity of less than 30 Pa×s, preferably less than 20 Pa×s, more preferably less than 10 Pa×s at 65°C according to DIN 54458. Even more advantageously, the printable structural adhesive composition exhibits a viscosity of less than 30 Pa×s, preferably less than 20 Pa×s, more preferably less than 10 Pa×s at 65°C according to DIN 54458.
[0036] Epoxy resin
[0037] The printable structural adhesive composition comprises at least one epoxy resin. There is no particular limitation on the epoxy resin used herein. An epoxy resin is a polymer having one or more epoxy functional groups. Typically, but not exclusively, the polymer comprises repeating units derived from monomers having epoxy functional groups, but the epoxy resin may also include, for example, silicone-based polymers comprising epoxy groups, or organic polymer particles coated with epoxy groups or modified therefrom, or particles coated with epoxy-containing polymers or dispersed therein or modified therefrom. The epoxy functional groups allow the resin to undergo a crosslinking reaction. The epoxy resin may have an average epoxy functionality of at least 1, greater than 1, or at least 2. In a preferred aspect, the average epoxy equivalent of the epoxy compound used herein is less than 250 g / equivalent, preferably less than 230 g / equivalent, more preferably less than 220 g / equivalent, and even more preferably less than 200 g / equivalent. Preferably, the average epoxy equivalent of the epoxy compound used herein is comprised between 100 g / equivalent and 200 g / equivalent, preferably between 150 g / equivalent and 200 g / equivalent, more preferably between 170 g / equivalent and 200 g / equivalent. Still preferably, the weight average molecular weight of the epoxy compound used herein does not exceed 700 g / mol, preferably does not exceed 500 g / mol, more preferably does not exceed 400 g / mol. Advantageously, the weight average molecular weight of the epoxy compound used herein is comprised between 200 g / mol and 400 g / mol, preferably between 300 g / mol and 400 g / mol, more preferably between 350 g / mol and 400 g / mol. The epoxy compound used herein is preferably selected from epoxy compounds having at least 2, and more preferably 2 to 4 average epoxy functional groups per molecule (i.e., the average number of polymerizable epoxy groups per molecule).
[0038] Any epoxy resin generally known to those skilled in the art can be used in the context of the present disclosure. The epoxy resin can be aromatic, aliphatic, alicyclic or a mixture thereof. In typical aspects, the epoxy resin used herein is aromatic. Preferably, the epoxy resin contains a glycidyl or polyglycidyl ether type moiety. Such moieties can be obtained, for example, by the reaction of a hydroxyl functional group (such as but not limited to a dihydric or polyhydric phenol or a fatty alcohol including a polyol) with an epichlorohydrin functional group. As described herein, a dihydric phenol is a phenol containing at least two hydroxyl groups (also referred to as "aromatic" hydroxyl groups) bonded to an aromatic ring of the phenol or, in the case of a polyphenol, at least two hydroxyl groups bonded to an aromatic ring. This means that the hydroxyl groups can be bonded to the same ring of the polyphenol or to different rings of the polyphenol. Therefore, the term "dihydric phenol" is not limited to phenols or polyphenols containing two "aromatic" hydroxyl groups, but also encompasses polyphenols, i.e., compounds having more than two "aromatic" hydroxyl groups.
[0039] Examples of useful dihydric phenols include resorcinol, catechol, hydroquinone, and polyphenols including p,p'-dihydroxybibenzyl, p,p'-dihydroxyphenyl sulfone, p,p'-dihydroxybenzophenone, 2,2'-dihydroxyphenyl sulfone, p,p'-dihydroxybenzophenone, 2,2-dihydroxy-1,1-dinaphthylmethane, and the 2,2', 2,3', 2,4', 3,3', 3,4', and 4,4' isomers of dihydroxydiphenylmethane, dihydroxydiphenyldimethylmethane, dihydroxydiphenylethylmethylmethane, dihydroxydiphenylmethylpropylmethane, dihydroxydiphenylethylphenylmethane, dihydroxydiphenylpropenylphenylmethane, dihydroxydiphenylbutylphenylmethane, dihydroxydiphenyltolylethane, dihydroxydiphenyltolylmethylmethane, dihydroxydiphenyldicyclohexylmethane, and dihydroxydiphenylcyclohexane.
[0040] Preferred epoxy resins include epoxy resins containing or consisting of glycidyl ethers or polyglycidyl ethers of dihydric or polyhydric phenols, such as, but not limited to, bisphenol A, bisphenol F, and combinations thereof. They contain one or more repeating units derived from bisphenol A and / or F. Such ethers or such repeating units can be obtained, for example, by polymerization of glycidyl ethers of bisphenol A and / or F with epichlorohydrin. Epoxy resins of the diglycidyl ether type of bisphenol A can be represented by formula (1), wherein n represents a repeating unit (when n=0, the formula represents the diglycidyl ether of bisphenol A):
[0041]
[0042] Typically, epoxy resins are blends of several resins. Therefore, n in the above formula may represent an average value of the blend and may not be an integer, but may include values such as, but not limited to, 0.1 to 2.5.
[0043] Instead of the above aromatic epoxy resin, or in addition to the above aromatic epoxy resin, a fully or partially hydrogenated derivative (i.e., the corresponding alicyclic compound) of the above aromatic epoxy resin may also be used. Instead of or in addition to the aromatic epoxy resin, an aliphatic, for example, acyclic, linear or branched epoxy resin may also be used.
[0044] Typically, the epoxy resin is a liquid. The epoxy resin may include a solid epoxy resin used in a dissolved form or dispersed in, for example, another liquid resin. Preferably, the epoxy resin is a liquid under ambient conditions (23° C., 1 bar). The epoxy resin may contain halogens, preferably bromine atoms to make them non-flammable. Preferably, at least one epoxy resin is selected from phenolic epoxy resins, bisphenol epoxy resins, hydrogenated epoxy resins, aliphatic epoxy resins, halogenated bisphenol epoxy resins, novolac epoxy resins, and any combination and mixture thereof.
[0045] Examples of suitable and commercially available epoxy resins include diglycidyl ethers of bisphenol A (available under the trade names EPON 828, EPON 830, EPON 1001, or EPIKOTE 828 from Hexion Specialty Chemicals GmbH, Rosbach, Germany, or under the trade names DER-331 or DER-332 from Dow Chemical Co,); diglycidyl ethers of bisphenol F (e.g., EPICLON 830 from Dainippon Ink and Chemicals, Inc. or DER-354 from Dow Chemical Co, Schwalbach / Ts., Germany); diglycidyl ethers of blends of bisphenol A and bisphenol F (e.g., DER-354 from Momentive Specialty Chemicals, Columbus, USA); Chemicals, Columbus, USA). Other bisphenol-based epoxy resins are commercially available under the trade name EPILOX (Leuna Epilox GmbH, Leuna, Germany); flame retardant epoxy resins are commercially available under the trade name DER 580 (brominated bisphenol-type epoxy resin available from Dow Chemical Co.). Cycloaliphatic epoxy resins are commercially available under the trade name EPINOX (Hexion Specialty Chemicals GmbH). In addition, the adhesive composition as described herein may include at least one solid epoxy resin and / or at least one liquid epoxy resin. The adhesive composition as described herein may also include additional ingredients, such as a toughening agent mixed with the epoxy resin or contained in the epoxy resin. For example, the printable structural adhesive composition according to the present disclosure may contain at least one solid epoxy resin in an amount ranging from 1 wt % to 25 wt %, preferably 2 wt % to 20 wt %, more preferably 3 wt % to 15 wt %; at least one liquid epoxy resin in an amount ranging from 1 wt % to 1 wt % to 25 wt %, preferably 2 wt % to 20 wt %, more preferably 3 wt % to 15 wt %; at least one epoxy resin containing at least one toughening agent in an amount ranging from 20 wt % to 80 wt %, preferably 25 wt % to 75 wt %, more preferably 30 wt % to 70 wt %; all ranges of amounts are relative to the total weight of the structural adhesive composition.
[0046] Epoxy Curing Agent
[0047] The printable structural adhesive film according to the present disclosure comprises at least one epoxy curing agent. Any epoxy curing agent generally known in the art can be used in the thermosetting composition of the structural adhesive film of the present invention. Epoxy curing agents suitable for use herein are substances that react with the oxirane ring of an organic epoxide to cause the epoxide to undergo significant crosslinking. These substances contain at least one nucleophilic or electrophilic moiety (e.g., an active hydrogen atom) that causes a crosslinking reaction to occur. Epoxy curing agents are different from epoxide chain extenders, which are primarily embedded between the chains of the organic epoxide and induce little (if any) crosslinking. Epoxy curing agents as used herein are also referred to in the art as epoxy hardeners, epoxide hardeners, catalysts, epoxy curing agents, and curing agents.
[0048] Sometimes, a distinction is made between epoxy curing agents and accelerators used to increase the rate of the epoxy curing reaction. Accelerators are generally multifunctional substances that can also be classified as epoxy curing agents. Therefore, in this specification, no distinction is made between curing agents and accelerators.
[0049] Epoxy curing agents for use herein include those that are commonly used to cure epoxy resin compositions and form a cross-linked polymer network. Suitable epoxy curing agents may also be referred to as latent curing agents, which are generally selected so that they do not react with epoxy resins before applying appropriate processing conditions. Such compounds also include aliphatic and aromatic tertiary amines such as dimethylaminopropylamine and pyridine, which can serve as catalysts to generate significant crosslinking. In addition, boron complexes can be used, especially with monoethanolamine, imidazoles such as 2-ethyl-methylimidazole, guanidines such as tetramethylguanidine, dicyandiamide (often referred to as DICY), substituted ureas such as toluene diisocyanate urea, aliphatic ureas or diphenyl dimethyl urea, and anhydrides such as 4-methyltetrahydroxyphthalic anhydride, 3-methyltetrahydroxyphthalic anhydride and methylnorbornene phthalic anhydride. Other available epoxy curing agents include polyamines, mercaptans and phenols. Other epoxy curing agents for use herein include encapsulated amines, Lewis acid salts, transition metal complexes and molecular sieves. Preferably, the epoxy curing agent is selected from amines, anhydrides, guanidines, dicyandiamide and mixtures thereof. More preferably, the epoxy curing agent comprises dicyandiamide. Epoxy curing agents suitable for use herein may be obtained under the trade name CG-1200 or Dyhard100com Alzchem are commercially available from Air Products. Exemplary polyetheramines suitable for use herein are commercially available from Huntsman Chemicals under the trade name JEFFAMINE or from BASF, Ludwigshafen Germany under the trade name TTD (4,7,10-trioxytridecane-1,13-diamine). The polyamidoamine may be a branched or unbranched aromatic polyamidoamine or a branched or unbranched aliphatic polyamidoamine. Preferably, the polyamidoamine is an aliphatic polyamidoamine. The polyamidoamines that may be advantageously used in the context of the present disclosure are obtained as described in
[0010] to
[0029] of EP 249527A1, the disclosure of which is incorporated herein by reference.
[0050] The amount of epoxy curing agent in the thermosetting composition of the structural adhesive composition is generally comprised between 1 wt % and 15 wt %, preferably 2 wt % to 12 wt %, more preferably 3 wt % to 9 wt %, based on the total weight of the structural adhesive composition.
[0051] Toughening agent
[0052] The printable structural adhesive composition according to the present disclosure comprises at least one toughening agent. As is generally known in the art, the term "toughening agent" can be used interchangeably with the term "impact modifier". Even at lower temperatures, the use of an impact modifier or toughening agent will also have the effect of improving the impact resistance of the cured structural adhesive composition. That is, the cured structural adhesive composition is tougher or toughened. Therefore, the cured printable structural adhesive composition described herein comprising at least one toughening agent can exhibit a higher overlap shear strength (according to DIN EN 1465) and / or adhesive peel strength (according to DIN EN 1464) than a comparable structural adhesive composition not containing the at least one toughening agent.
[0053] Any toughener generally known in the art can be used in the expandable structural adhesive film according to the present disclosure. The at least one impact modifier is preferably selected from the group comprising: core-shell toughener, CTBN (carboxyl and / or nitrile terminated butadiene / nitrile rubber) and high molecular weight amine terminated polybutylene oxide, and any combination and mixture thereof. Particularly preferred core-shell impact modifiers generally contain different materials in the core region and the shell region, respectively. Preferably, the core can be harder than the shell, but this is not necessary. The shell can contain harder materials and / or the structure of the shell can be layered. Most preferably, the internal hard core component is composed of the following substances: a single and / or multiple organic polymers; inorganic oxides from the first, second and / or third transition series of the periodic table, such as silicon dioxide, aluminum oxide, zirconium oxide; and / or naturally occurring minerals, such as feldspar, silicates, aluminates, zirconates; and / or other hardening substances, such as carbides, nitrides, silicides, aluminides; and / or some combinations thereof and between the two. The outer soft shell component may be composed of rubbers such as dienes, olefin rubbers, natural rubber, polyisoprene, copolymers thereof, ethylene propylene monomer rubbers, diene-acrylonitrile copolymers, copolymers of vinyl aromatic monomers, styrene-butadiene copolymers known as SBR rubbers, and terpolymers of dienes with acrylonitrile or unsaturated esters and styrene or vinyl toluene. The soft shell preferably comprises a modifier having functional groups such as carboxyl, hydroxyl, epoxy, cyanate, isocyanate, amino and thiol that are reactive with the epoxy component of the precursor. Core-shell impact modifiers useful for expandable structural adhesive films are commercially available, for example, under the trade name Paraloid TM Commercially available from Rohm and Hass. During the curing process, CTBN tougheners react with the epoxide component of the precursor via their carboxyl and / or nitrile functional groups, thereby incorporating their butadiene / nitrile rubber portions as soft, vibration-absorbing segments into the epoxy network that forms the hard segments. CTBN tougheners / impact modifiers useful in the present disclosure may be, for example, marketed under the trade name "Albipox TM " is commercially available from Hanse Chemie AG, Hamburg, Germany. Similarly, high molecular weight amine-terminated polybutylene oxides that can be used in the structural adhesive films described herein are commercially available, for example, from 3M Company, St. Paul / MN, USA under the trade name "3M EPX TMPreferably, the at least one toughening agent comprises at least one first toughening agent and at least one second toughening agent different from the at least one first toughening agent. This can have the effect of improving toughening over a wider temperature range. The amount of at least one impact modifier in the structural adhesive composition as disclosed herein is preferably in the range of 10 wt % to 50 wt %, preferably between 15 wt % and 45 wt %, more preferably between 20 wt % and 40 wt %, based on the total weight of the printable structural adhesive composition.
[0054] In some embodiments, the toughening agent (eg, core-shell toughening agent) particles have a particle size of less than 1 micron, 500 nanometers, or 250 microns.
[0055] In some embodiments, the composition comprises a combination of two or more toughening agents with different properties. In some embodiments, the composition comprises up to 10% by weight of toughening agent particles with a particle size (e.g., average particle size) greater than 1 micron, 5 microns, 10 microns, 15 microns, or 20 microns and toughening agent particles with a particle size (e.g., average particle size) less than 1 micron. The particle size of core-shell toughening agents (e.g., MX type) is described in the supplier data sheet. Scanning electron microscopy (SEM) (e.g., Thermo Scientific TM Phenm TM The particle size is determined by determining the average particle size (d50) using a desktop SEM) and software (e.g., Thermo Scientific Phenom ParticleMetric software). The equivalent circle diameter can be used as a parameter for measuring particle size. Typically, less than 50 particles are measured in one SEM image to determine the average particle size.
[0056] In some embodiments, tougheners (e.g., smaller tougheners) can have an average particle size (D50) of at least 50 nanometers, 75 nanometers, or 100 nanometers. In some embodiments, tougheners (e.g., smaller tougheners) can have an average particle size of at least 150 nanometers or 200 nanometers. In some embodiments, tougheners (e.g., smaller tougheners) can have an average particle size of no more than 750 microns or 500 microns. In some embodiments, tougheners (e.g., smaller tougheners) can include particles with a size range of 50 nanometers to 500 nanometers. Tougheners (e.g., smaller tougheners) can include a mixture of first particles with a D50 in the range of 50nm to 150nm (e.g., 100nm) and second particles with a D50 greater than 150nm to 300nm (e.g., 200nm). In some embodiments, the composition comprises at least 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, or 65 wt% of a toughener (e.g., a smaller toughener). In some embodiments, the composition comprises no more than 75 wt%, 70 wt%, 65 wt%, 60 wt%, 55 wt%, or 50 wt% of a toughener (e.g., a smaller toughener). In some embodiments, the toughener (e.g., a smaller toughener) has a glass transition temperature (Tg) of at least -40°C, -35°C, -30°C, -25°C, or -20°C. The toughener (e.g., a smaller toughener) may have a Tg of no more than -10°C, -15°C, or -20°C. In some embodiments, the toughener (e.g., a smaller toughener) comprises a core-shell toughener containing a polybutadiene core. Suitable toughening agents include core-shell rubbers in liquid epoxy resins based on bisphenol-A, available from Kaneka, Westerlo, Belgium, under the trade designation "KANE ACE MX-153", having a polybutadiene polymer core, a D50 particle size of 100 nm, and a Tg between -40°C and -20°C. Another suitable toughening agent includes a core-shell rubber in a liquid epoxy resin based on bisphenol-A epoxide, available from Kaneka, Westerlo, Belgium, under the trade designation "KANE ACE MX-257", having a polybutadiene polymer core, a D50 particle size of 200 nm, and a Tg between -40°C and -20°C.
[0057] Tougheners (e.g., larger tougheners) can have an average particle size (D50) of at least 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, or 35 microns. In some embodiments, tougheners (e.g., larger tougheners) can have an average particle size of no more than 100 microns, 75 microns, or 50 microns. In some embodiments, the composition comprises at least 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt% of tougheners (e.g., larger tougheners). In some embodiments, the composition comprises no more than 20 wt%, 15 wt%, or 10 wt% of tougheners (e.g., larger tougheners). In some embodiments, tougheners (e.g., larger tougheners) have a glass transition temperature (Tg) lower than -40°C, -45°C, or -50°C. The toughening agent (e.g., a larger toughening agent) may have a Tg of at least -75°C, -70°C, -65°C, -60°C, -55°C, or -50°C. In some embodiments, the toughening agent (e.g., a larger toughening agent) comprises a methyl methacrylate / butadiene / styrene copolymer. Suitable toughening agents include methyl methacrylate / butadiene / styrene copolymers available from Kaneka of Westerlo, Belgium under the trade name "KANE ACE B-564" with a D50 particle size of 35 microns and a Tg of -50°.
[0058] Reactive diluent
[0059] It is also preferred that the printable structural adhesive composition according to the present disclosure comprises an epoxy-based reactive diluent. The reactive diluent is an epoxy-containing molecule. There are no particular limitations on the epoxy-based reactive diluents used herein. Any epoxy-based reactive diluent commonly known in the art may be used in the context of the present disclosure.
[0060] Without wishing to be bound by theory, it is believed that epoxy-based reactive diluents particularly advantageously affect the flow characteristics of the printable structural adhesive compositions as described herein.
[0061] In a particular aspect of the present disclosure, the epoxy-based reactive diluents used herein have a saturated or unsaturated cyclic backbone, and preferably contain a glycidyl ether as a reactive terminal moiety.
[0062] According to a preferred aspect, the epoxy reactive diluent used herein is selected from the group consisting of diglycidyl ether of resorcinol, diglycidyl ether of cyclohexanedimethanol, diglycidyl ether of neopentyl glycol, triglycidyl ether of trimethylolpropane, and any mixture thereof.
[0063] Commercially available reactive diluents for use herein include, for example, "Reactive Diluent 107" (available from Hexion), the "Epodil" series (available from Air Products and Chemical Inc, Allentown, PA, USA), specifically including EPODIL 746, EPODIL 747, EPODIL 748 and EPODIL 757, and reactive diluents from ipoxy Chemicals GmbH, Germany.
[0064] Preferably, at least one toughening agent is included in the printable structural adhesive composition in an amount ranging from 10 wt % to 50 wt %, preferably from 15 wt % to 45 wt %, more preferably from 20 wt % to 40 wt %, based on the total weight of the structural adhesive composition.
[0065] Packing material
[0066] In addition, the printable structural adhesive composition may include at least one filler material. However, it may also be advantageous not to include any filler material in the printable structural composition described herein. Therefore, in a preferred embodiment, the printable structural adhesive composition according to the present disclosure does not include a filler material. Filler materials that can be used in adhesive compositions are known in the art and are selected from mineral fillers, silica and glass beads. The silica compound may have the effect of improving the fluidity, processability and increase of the composition as described herein without sacrificing the mechanical strength or water resistance of the cured coating obtained therefrom. In this regard, it is preferred that the at least one silica compound is selected from fused silica, pyrogenic silica, perlite and any combination and mixture thereof. The silica compound as described herein may preferably be used in the form of silica particles. Preferably, the silica particles include pyrogenic silica, preferably hydrophobic pyrogenic silica, fused silica, amorphous silica particles, hollow silica particles, silica gel, calcium silicate, and any combination thereof. Exemplary commercial fillers include SHIELDEXAC5 (a synthetic amorphous silica, calcium hydroxide mixture available from WR Grace (Columbia, MD, USA); CAB-O-SIL TS 720 (a hydrophobic fumed silica treated with a polydimethylsiloxane polymer available from Cabot GmbH (Hanau, Germany); AEROSIL VP-R-2935 (a hydrophobic fumed silica available from Degussa (Düsseldorf, Germany); Germany); AEROSIL R-202 (hydrophobic fumed silica, available from Evonik Industries, Germany); Glass beads type IV (250-300 microns): amorphous silica (available from 3M Deutschland GmbH, Neuss, Germany); Fusil SF 20 (available from 3M.510 Midway, Tennessee, USA); amorphous fused silica; and APYRAL 24ESF (epoxysilane functionalized (2 wt%) aluminum trihydrate, available from Nabaltec GmbH (Schwandorf, Germany). Fused silica is available, for example, from 3M, USA under the trade name Fusil.
[0067] method
[0068] The present disclosure also provides a method for applying an adhesive to a substrate, the method comprising the steps of:
[0069] (i) providing a printable structural composition according to any one of the preceding claims;
[0070] (ii) printing the printable structural adhesive composition onto a first substrate;
[0071] (iii) optionally, repeating step (ii);
[0072] (iv) optionally, placing a second substrate on top of the structural adhesive composition on the first substrate;
[0073] (v) performing a curing step to cure the printable structural adhesive composition.
[0074] Due to the properties of the structural adhesive composition according to the present disclosure, in particular having a viscosity within the range as described herein, applying the structural adhesive composition is performed by printing it onto the surface of the first substrate. This is highly advantageous compared to applying the structural adhesive by extruding a paste due to increased speed, improved precision, improved control over the amount or thickness of the adhesive applied, and / or due to the use of fast robotic equipment, preferably computer-controlled equipment.
[0075] Printing can be carried out by any method known in the art. Preferably, the printing in step (ii) includes spray printing, pad printing, screen printing and / or orifice printing. These printing methods provide advantages as described herein, and can be selected and adjusted according to the intended use, surface structure, surface area to be covered and / or the thickness of the pattern to be applied. Preferably, printing is carried out by printing a structural adhesive composition having a temperature in the range of 20°C to 90°C, preferably 25°C to 85°C, more preferably 30°C to 80°C. Lower temperatures may lead to an undesirable increase in viscosity, while higher temperatures may even reduce the viscosity more, or even lead to partial pre-curing of the adhesive or undesirable side reactions.
[0076] In one aspect of the method according to the present disclosure, it is preferred that printing includes jet printing, preferably performed by an application head of an automated robotic device. As used herein, jet printing means applying a printable structural adhesive composition via a non-contact drop-on-demand inkjet printing method. Typically, the structural adhesive composition described herein is deposited on the surface of the first surface in the form of small droplets or even microdroplets. Therefore, the fact that the printable structural adhesive is printed by jet printing while maintaining excellent adhesive properties exhibits a wide range of very attractive benefits, such as non-contact, on-demand, high frequency (which is equal to high throughput), accuracy, and can be combined with full automation. In addition, the small and consistent size of the droplets in the jet printing (usually 0.2mm-1.5mm) leads to accurate deposition and actually eliminates material waste. Finally, the potential control of a single nozzle on the jetting device enables the fine deposition of complex and unlimited patterns and form factors. This is particularly attractive because the "printed" pattern can be modified to suit customer needs and new applications. All of these advantages lead to time saving and effective use of structural adhesives (faster adhesive application, shorter cycles, and smaller rework / corrections), which translates into cost savings in the automotive industry. This is also very advantageous in view of the general desire in the automotive industry to reduce vehicle weight.
[0077] The spray printing as described herein is preferably carried out by the application head of the automated robot device. This has the advantages of speed, precision and control, particularly by a computer and corresponding software. Preferably, the application head includes at least one piezoelectric valve. This is particularly advantageous because the opening and closing time of the valve is very fast, thereby enabling the deposition of very small droplets, which greatly benefits the precision and possibility of printing a small pattern determined. Typically, spray printing means that the printable structural adhesive composition is dropwise applied to the first substrate. Preferably, the dropwise printing of the printable structural adhesive composition is carried out in a manner that beads, line structures and / or regions are formed on the surface of the first substrate. Beads, lines, structures and / or regions can be formed on the same level on the first substrate, or formed on the top of previously formed beads, lines, structures and / or regions.
[0078] When two substrates are to be bonded, printing by jet printing is preferably performed. This is the most common situation in the bonding operation of the automotive industry. Therefore, preferably, step (iv) includes placing the second substrate on top of the structural adhesive composition on the first substrate. The first substrate and / or the second substrate may include a material selected from metal, carbon fiber, glass fiber and composite material. In particular, the first substrate and / or the second substrate may include a steel plate or an aluminum plate. Preferably, the method as described herein includes a roll-to-roll bonding process as known in the automotive industry. In the roll-to-roll process, the printable structural adhesive produces the following advantages: it bonds the first substrate and the second substrate together and seals the roll-to-roll.
[0079] In another aspect of the method of the present disclosure, the printing in step (ii) comprises pad printing. Pad printing comprises printing a printable structural adhesive on a defined area of the surface of the first substrate. In particular, pad printing is very advantageous in applications involving flat designs, such as cooling plates in EV battery cooling systems (such as heat exchangers) with large and complex bonding areas. When compared with other standard dispensing techniques, pad printing provides advantages in terms of speed and cycle time. For example, a dispensing nozzle will take much longer because the dispensing nozzle is required for all areas where the adhesive must be applied by a robot. Therefore, pad printing is particularly advantageous in EV segmentation and EV assembly (including battery assembly), battery cell bonding, cover sealing, cooling pipe and channel bonding. The surface of the first substrate can be selected from a flat surface, a cylindrical surface, a spherical surface, a compound angle surface, a textured surface, a concave surface or a convex surface. Preferably, the method comprising pad printing as described herein comprises bonding, joining and sealing of components of batteries, fuel cells, electronic components and / or photovoltaic systems. It is also preferred that the method comprising pad printing as described herein comprises bonding, bonding, cover sealing, cooling pipe and / or channel bonding.
[0080] In another aspect of the method according to the present disclosure, the printing in step (ii) includes screen printing and / or orifice printing. This is advantageous because screen printing, as a method of applying a structural adhesive as described herein, can achieve high precision and short cycle time while controlling the volume of adhesive effectively applied to the first surface. In addition, the order of printing and curing can be considered as an in-situ curing order. The final shape of the printed and cured adhesive as described herein can then be used as a seal, even in demanding applications with respect to mechanical stress, temperature, and exposure to aggressive chemicals. Screen printing and / or orifice printing itself are well known to those skilled in the art. Preferably, the method including screen printing and / or orifice printing as described herein includes bonding, joining and sealing of components of a battery, a fuel cell, an electronic component, and / or a photovoltaic system. In this regard, the method preferably includes bonding between battery cells, cover sealing, cooling pipes, and / or channel bonding. In step (ii), the printable structural adhesive composition provides an adhesive layer and / or a sealant. Preferably, the adhesive layer and / or the sealant form at least a portion of the sealant in the battery or fuel cell. Typically, the adhesive layer and / or sealant can form at least a portion of a sealant in PEM fuel cell seals, PEM fuel electrolysis system seals, alkaline fuel cells, direct methanol fuel cells, battery seals, membrane seals, pump seals, oven seals, and housing seals for electronic devices and power electronic devices.
[0081] The heating during the curing step can be performed in various ways known to the skilled person. In particular, the heating steps already present in the existing assembly process (e.g., in the automotive industry) can be used for this purpose. For example, the curing step (IV) can occur in parallel with the curing of the paint or coating in the paint oven used in the automotive industry. Therefore, it is preferred that the curing step (IV) comprises a heating treatment selected from induction heating, convection heating, IR heating, ultrasonic treatment, microwave heating, laser treatment, welding treatment and / or resistance heating, Joule heating, ohmic heating and any combination thereof. It is also preferred that the curing step comprises convection heating, IR heating and / or welding treatment, preferably convection heating. Conventional heating occurs in paint ovens commonly used in the automotive industry, for example. With regard to the temperature applied in the curing step (IV) in the method according to the present disclosure, it is preferred that the temperature is at least 150°C, preferably at least 160°C, more preferably at least 170°C. Preferably, the temperature in the curing step (IV) is 250°C and lower, preferably 240°C and lower, more preferably 230°C and lower. It is therefore preferred that the temperature in the curing step (IV) is in the range of 150°C to 250°C, preferably 160°C to 240°C, more preferably 170°C to 230°C. If the printable structural adhesive composition has firm contact with the first metal panel, i.e. substantially all on one of its major surfaces, it expands during this heating step, also contacting the second metal panel, and filling any gap therebetween. This has the effect that the first metal panel and the second metal panel are adhesively connected. Moreover, the assembly is effectively sealed. In particular sealing against water and the like is advantageous, since effective protection against corrosion is provided.
[0082] The present disclosure also provides the use of printable structural adhesive compositions as described herein for bonding and / or sealing in industrial manufacturing operations. Typically, the use includes printing the printable structural adhesive composition onto at least one substrate. Preferably, printing is performed by automated equipment or robotic equipment. In this regard, preferably, printing includes pad printing, spray printing, screen printing and / or stencil printing. Preferably, the use includes sealing operations in chemical and / or temperature challenge environments, preferably selected from the manufacture of PEM fuel cell seals, PEM fuel electrolysis system seals, alkaline fuel cells, direct methanol fuel cells, battery seals, membrane seals, pump seals, oven seals and electronic devices and power electronic devices housing seals. Preferably, the use includes the manufacture of heat exchangers in cooling plates, cooling systems, preferably electronic devices (preferably batteries). Further preferably, the use includes battery assembly, preferably battery bonding, cover sealing, manufacturing and / or channel bonding of cooling pipes.
[0083] The present disclosure also provides for the use of a printable structural adhesive composition as described herein for repairing holes in an electrophoretically coated automobile body or parts thereof.
[0084] Figure 3 Schematic diagram of an automated process for electrophoretic coating of an automobile body 300. Electrophoretic coating (e.g., E-coating) is a wet paint finishing method that protects metals (e.g., steel) from corrosion. E-coating is commonly used in the automotive industry for corrosion protection of metal automobile bodies and their components. A typical E-coating process includes a pretreatment in which the metal surface is thoroughly cleaned (including degreasing) and then a phosphate solution is applied. The phosphate-treated metal automobile body is then immersed in an electrodeposition tank containing an electrophoretic coating bath. The electrophoretic coating bath may contain, for example, 80%-90% deionized water and 10%-20% coating solids. The coating solids include durable and tough materials that resist corrosion, such as acrylic and / or epoxy resins, and typically include color pigments. After the electrophoretic coating bath is applied to the metal surface, the surface is rinsed with deionized water to remove excess unbonded electrophoretic coating bath. The rinse solution is collected in a rinse tank and may be filtered and recycled back into the electrodeposition tank. The electrophoretically coated metal surface is then placed in an oven to cure the resin. In one embodiment, the electrophoretically coated metal surface may be cured for approximately 20 minutes at 375° F. In other embodiments, other durations and temperatures may be utilized.
[0085] refer to Figure 1 , the automobile body 100 typically has a plurality of holes 150. Some of the holes correspond to locations for mechanically attaching other components such as interior panels, storage compartments, electronics, vents, etc. Other holes are typically present for the purpose of effectively draining the electrophoretic paint bath and rinsing and / or reducing the weight of the automobile body. Holes that do not have the intended mechanical attachment function are repaired prior to subsequent paint applications (e.g., primer, basecoat, and clearcoat coatings).
[0086] In one embodiment, a method for repairing a hole in an electrophoretically coated automobile body or a component thereof is described, the method comprising selecting a hole in the electrophoretically coated automobile body or a component thereof; applying a first substrate and a printable structural adhesive as described herein such that the substrate covers the hole and the adhesive is disposed between the substrate and the surface of the electrophoretically coated automobile body or a component thereof at the location of the hole; and curing the adhesive.
[0087] The patch substrate can have a variety of shapes. In a typical embodiment, the patch substrate has a similar shape, but is sufficiently large compared to the hole. The patch is bonded to a sufficient surface area of a second substrate (e.g., an electrophoretically coated automobile body or part thereof) so that the desired mechanical strength is achieved. In some embodiments, the patch substrate is circular in shape, such as Figure 2The first substrate and / or the second substrate may comprise a material selected from metal, carbon fiber, glass fiber and composite materials, as described above. The first substrate may alternatively comprise an organic material having a sufficiently high melting point so that it does not melt during curing of the electrophoretic coating material.
[0088] refer to Figure 2 , the printable structural adhesive can be applied to a first substrate 220, ie, the substrate of the patch; and / or the printable structural adhesive can be applied to a second substrate 230 including holes 250, such as an electrophoretically coated automobile body or part thereof.
[0089] In embodiment (a), a printable structural adhesive 270 is applied to a peripheral portion of a first substrate 225 (e.g., a circular first substrate) to form an adhesive-coated patch 275. The adhesive-coated patch is then contacted with a second substrate 230 (e.g., an electrophoretically coated automobile body or part thereof) to bond the first substrate to the second substrate at the location (e.g., peripheral location) of the hole 250. In embodiment (b), a printable structural adhesive 270 is applied to a peripheral portion of a hole 250 of a second substrate 230 (e.g., an electrophoretically coated automobile body or part thereof), and the first substrate 225 (e.g., a circular first substrate) is contacted with the second substrate 230 at the location (e.g., peripheral location) of the hole 250. The first substrate of the patch covers the hole, and the printable structural adhesive is disposed between the surfaces of the first substrate and the second substrate (e.g., an electrophoretically coated automobile body or part thereof) at the location of the hole.
[0090] Re-reference Figure 3 , curing the structural adhesive can be performed before, during, or after the electrophoretically coated automobile body is transferred to the E-coat oven. In some embodiments, the hole is patched before the electrophoretically coated automobile body is transferred to the E-coat oven. The E-coated surface of the patch and the printable structural adhesive can be cured simultaneously using the same curing conditions used to cure the E-coat.
[0091] refer to Figure 5A In another embodiment, a method for repairing a hole in an electrophoretically coated automobile body or a component thereof is described, the method comprising receiving data regarding the location of a hole in the electrophoretically coated automobile body or a component thereof (510); and using the data to repair the hole using a first substrate (e.g., a patch) and an adhesive (550).
[0092] refer to Figure 5B, the method may include receiving data including detecting one or more holes using an imaging system (501). Alternatively or in addition, the method may include receiving data including analyzing a CAD drawing of a second substrate (e.g., an automobile body or a component thereof) including one or more holes (502).
[0093] refer to Figure 5C The method may further include a user interface adapted to select one or more holes of the image provided by the imaging system or the CAD drawing. Alternatively or in addition, the method may further include a user interface adapted to confirm a computer-generated selection of one or more holes of the image provided by the imaging system or the CAD drawing.
[0094] refer to Figure 6 , a method utilizing data can include applying an adhesive to a surface of a first substrate (e.g., a first substrate of a patch) and / or a second substrate (e.g., an electrophoretically coated automobile body or component thereof) at a location proximate to the hole using a robotic fluid dispenser.
[0095] refer to Figure 7 , the method using the data may include applying an adhesive (optionally with a robotic fluid dispenser) to the surface of a first substrate (e.g., the first substrate of the patch) and / or a second substrate (e.g., an electrophoretically coated automotive body or part thereof) at the location of the hole. In this embodiment, the method also includes contacting the first substrate (e.g., the first substrate of the patch) with the second substrate (e.g., the electrophoretically coated automotive body or part thereof) with a robotic pick and place system so that the first substrate covers the hole, and the adhesive is disposed between the substrate and the surface of the electrophoretically coated automotive body or part thereof at a location near the hole.
[0096] refer to Figure 8 In another embodiment, a non-transitory computer-readable medium stores one or more instructions that, when executed by a processor, cause the processor to: receive data regarding the location of a hole in an electrophoretically coated automotive body or component thereof; and utilize the data to cover the hole with a substrate and an adhesive disposed between the substrate and a surface of the electrophoretically coated automotive body or component thereof at the location of the hole.
[0097] A computer-readable medium 816 includes one or more computer-readable media, wherein each of the one or more computer-readable media is non-transient. The computer-readable medium may reside in, for example, an input device 806, a non-volatile memory 808, a volatile memory 810, or any combination thereof. The input device 806 may be an imaging system and / or a system including CAD drawing (e.g., CAD drawing of a car body or its parts), and a user interface for selecting and / or confirming data received by the imaging system or CAD drawing. The readable storage medium may include a tangible medium capable of storing instructions associated with a device or system or used by a device or system. Computer-readable media (also referred to herein as non-transient computer-readable media) include, as non-limiting examples: RAM, ROM, cache, optical fiber, EPROM / flash memory, CD / DVD / BD-ROM, hard drive, solid-state memory, optical or magnetic storage device, disk, electrical connection with wire, or any combination thereof. Non-transient computer-readable media may also include, for example, magnetic, optical, semiconductor, or electronic type systems or devices. Non-transitory computer readable media do not include carrier waves and / or propagated signals in any number of forms such as optical, electromagnetic, or a combination thereof.
[0098] about FIG. 5A to FIG. 8 It should be understood that although the printable structural adhesives described herein may be preferred, such methods may alternatively utilize other adhesive compositions.
[0099] Example
[0100] The present disclosure is further described, however, without wishing to limit the present disclosure thereto. The following examples are provided to illustrate certain embodiments but are not intended to be limiting in any way. Prior to this, some test methods for characterizing materials and their properties will be described. Unless otherwise indicated, all parts and percentages are by weight.
[0101] Test Method
[0102] Lap shear strength (OLS) according to DIN EN 1465
[0103] The surface of OLS metal sheets (steel, grade DX54+ZMB-RL1615, 0.8 mm thickness) was cleaned with n-heptane. Before testing, the metal sheets were placed at ambient room temperature (23°C + / - 2°C, 50% relative humidity + / - 5%) for 24 hours and the OLS strength was measured as described below.
[0104] According to DIN EN 1465, the Zwick Z050 tensile tester (commercially available from Zwick GmbH & Co. KG, Ulm, Germany) operated at a chuck speed of 10mm / min is used to measure the lap shear strength. For the preparation of the overlapping shear strength test assembly, the curable composition is placed on a surface of the prepared metal plate, and a little glass beads (diameter 0.30mm) are placed on the curable composition, to ensure that the thickness of the curable composition layer during the curing process is 0.30mm. Afterwards, the sample is covered by the second metal foil, so as to form a lap joint of 10mm. The lap joint is then clamped together using two binder clips, and after bonding, the test assembly is further stored at room temperature for 4 hours, and then placed in the air circulation oven from Heraeus (curing duration and temperature are taken from the embodiment part). The next day, the direct test sample. For each in the embodiment, three samples are measured, and the result is averaged and reported in units of MPa.
[0105] Wedge impact peeling according to ISO 11343
[0106] For the impact peel strength test, samples were prepared and tested according to ISO 11343 using a 30 mm x 20 mm bond area, 0.3 mm adhesive layer thickness and a test speed of 2 m / s. The substrate for the impact peel strength test was galvanized cold rolled steel. The curing conditions were set at 180°C for 30 minutes. Prior to testing, the cured test samples were stored at 23°C + / - 2°C, 50% relative humidity + / - 5% for 24 hours. Wedge impact peel values are reported in N / mm.
[0107] T-peel strength measurement according to DIN EN 14173
[0108] T-peel specimens were prepared using steel plates measuring 25 mm x 150 mm. The surface of the t-peel metal sheet (steel, grade DX54+ZMB-RL1615, 0.8 mm thickness) was cleaned with n-heptane. Prior to testing, the metal sheet was placed at ambient room temperature (23°C + / - 2°C, 50% relative humidity + / - 5%).
[0109] The t-peel force was measured for 24 hours as follows.
[0110] The T-peel force was determined according to DIN EN 14173 using a Zwick Z050 tensile tester (commercially available from Zwick GmbH & Co. KG, Ulm, Germany) operating at a crosshead speed of 100 mm / min.
[0111] For the preparation of t-peel test assembly, curable composition is placed on a surface of prepared metal plate, and a little glass beads (diameter 0.30mm) are placed on this curable composition, to ensure that the thickness of this curable composition layer is 0.30mm during the curing process. Then, cover sample with the second metal foil, thereby form the laminate of two metal foils, there is the adhesive layer of 25mmx100mmx0.3mm therebetween. Then use six binder clips that t-peel joint is clamped together, and after bonding, test assembly is further stored at room temperature for 4 hours, and then placed in the air circulation oven from Heraeus (curing duration and temperature are taken from the embodiment part). The second day, directly test sample. For each embodiment in the embodiment, three samples are measured, and the result is averaged and reported in N as unit.
[0112] Rheological tests according to DIN 54458
[0113] The rheological properties of the formulations were tested at 65° C. using an Anton Paar MCR 302 rheometer with 25 mm parallel plate geometry according to DIN 54458. A1 and A7 were determined to characterize the printability of the formulations.
[0114] Sample preparation :
[0115] The adhesive composition listed in Table 1 according to Example 1 was prepared as follows:
[0116] A one-component (1K) adhesive was formulated by mixing epoxy resin, DGEBA and 1001F and solids (Kaneka B-564 and dicyandiamide) in a Speedmixer cup (Speedmixer DAC 150600.2VAC-P, available from Hauschild Engineering, Germany) and mixing at 3500 rpm for 5 minutes. A homogeneous mixture was obtained. Then CSR masterbatch (Kaneka MX type) was added and the processor was processed again in the Speedmixer at 3500 rpm for 5 minutes. Finally, the liquid diluent RD24 was added to the formulation and the mixture was processed again in the Speedmixer at 3500 rpm for 5 minutes.
[0117] Table 1: Composition of Example 1 CSR = core-shell rubber; MB = masterbatch .
[0118]
[0119] The viscosity properties of Example 1 and a competitive 1K epoxy structural adhesive composition (Comparative Example 1) were tested for viscosity according to DIN 54458 at 65°C.
[0120] Table 2: According to DIN 54458 Test results of Example 1 and Comparative Example 1 at 65°C .
[0121]
[0122]
[0123] The mechanical bonding properties of the composition of Example 1 were tested. The results are summarized in Table 3.
[0124] Table 3: Mechanical properties of Example 1 .
[0125] Measurement results value OLSD IN EN 1465 20.5MPa T-Peel DIN EN 14173 160N i-Peel ISO 11343 39N / mm i-Peel ISO 11343 17.5N / mm
[0126] In addition, screen printing experiments were performed with the composition of Example 1. The screen was placed on top of an aluminum plate, and a scraper was used to push the adhesive through the screen and wet the substrate. No problems were encountered when the screen was subsequently removed. The pattern used on the screen was clearly visible on the aluminum plate. Thus, screen printing was successfully demonstrated for a printable structural adhesive according to the present disclosure.
[0127] Table 4: Composition of Example 3 .
[0128]
[0129]
[0130] The flowability (A1) viscosity of Example 3 according to DIN 54458 at 65° C. is 9.08 Pa×s.
[0131] The metal plates were electrophoretically coated with CathoGuard 800 (available from BASF). Holes of 30 mm diameter were formed in the electrophoretically coated metal plates. Patches were formed by cutting circles of 40 mm diameter from sheets of galvanized steel and aluminum (AlMg3). The thickness and weight were reported as follows. The adhesive of Example 3 was applied to the electrophoretically coated metal plates in a circle around the hole by a syringe to form beads of 1.0 mm in diameter and height. The patches were then pressed onto the adhesive with moderate force. Curing was carried out in an oven at 140°C for 25 minutes.
[0132] Table 5: Material thickness, dimensions of circular geometries and corresponding weights
[0133] Material and thickness Weight / g Steel, 0.3mm, d = 40mm 1.0g Steel, 0.6mm, d = 40mm 1.3g Aluminum, 0.75mm, d=40mm 1.6g PET, 0.1mm, d=40mm 0.2g PET, 1.0mm, d=40mm 1.7g
[0134] The adhesive strength of the patch was tested using a universal testing machine Zwick Z050 in compression mode. Figure 4The tool with a round tip is depicted with a specific geometry tool. The printed tool is clamped to the universal testing machine so that the round tip applies force to the adhesive bonded patch during the test. The electrophoretic coated plate with the repaired hole is clamped in the sample holder and the test speed is set to 10mm / min. The test is stopped when the travel path is 30mm (bending of the metal plate).
[0135] Table 6: Test results
[0136] Steel, 0.35mm Steel, 0.6mm Aluminum, 0.4mm Aluminum, 0.75mm PET, 3.0mm Force / N <![CDATA[460 1 ]]> <![CDATA[190 1 ]]> 75 <![CDATA[550 1 ]]> <![CDATA[1160 2 ]]>
[0137] 1 The test was stopped at high deformation of the electrophoretic coated panels 2 The electrophoretic coating is supported from below to withstand the high forces during testing
[0138] Table 7: T-peel strength measurement according to DIN EN 14173
[0139] Steel, 0.8mm Aluminum, 1.5mm 12N / mm 10N / mm
Claims
1. A printable structural adhesive composition, comprising: (a) at least one first epoxy resin; (b) at least one epoxy curing agent; (c) at least one toughening agent; The printable structural adhesive composition exhibits a viscosity of less than 100 Pa×s at 65° C. according to DIN 54458.
2. The printable structural adhesive composition according to claim 1, wherein the printable structural adhesive composition exhibits a viscosity of less than 80 Pa×s, preferably less than 60 Pa×s, more preferably less than 40 Pa×s at 65°C according to DIN 54458.
3. The printable structural adhesive composition according to claim 1 or 2, wherein the at least one toughening agent is selected from the group consisting of butadiene rubber, nitrile rubber, core-shell rubber, and any combination and mixture thereof.
4. The printable structural adhesive composition according to any one of the preceding claims, wherein the printable structural adhesive composition further comprises at least one reactive diluent.
5. A method for applying an adhesive to a substrate, the method comprising the steps of: (i) providing a printable structural composition according to any one of the preceding claims; (ii) printing the printable structural adhesive composition onto a first substrate; (iii) optionally, repeating step (ii); (iv) optionally, placing a second substrate on top of the structural adhesive composition on the first substrate; (v) performing a curing step to cure the printable structural adhesive composition.
6. The method according to claim 5, wherein the printing in step (ii) comprises spray printing, pad printing, screen printing and / or stencil printing.
7. The method according to claim 5 or 6, wherein in step (ii), printing is performed by printing the structural adhesive composition having a temperature in the range of 20°C to 90°C, preferably 25°C to 85°C, more preferably 30°C to 80°C.
8. A method according to any one of claims 5 to 7, wherein printing comprises jet printing, preferably by an application head of an automated robotic device.
9. The method according to claim 8, wherein the printable structural adhesive composition is applied dropwise onto the first substrate, preferably wherein dropwise printing of the printable structural adhesive composition is performed, thereby forming such beads, line structures and / or areas.
10. The method of claim 8 or claim 9, wherein the first substrate and / or the second substrate comprises a material selected from the group consisting of metal, carbon fiber, glass fiber, and a composite material.
11. The method of any one of claims 5 to 7, wherein pad printing comprises printing the printable structural adhesive on a defined area of a surface of the first substrate.
12. The method according to 11, wherein the surface of the first substrate is selected from a flat surface, a cylindrical surface, a spherical surface, a compound angle surface, a textured surface, a concave surface or a convex surface.
13. The method according to any one of claims 5 to 7, wherein the method comprises bonding, joining and sealing of components of batteries, fuel cells, electronic components and / or photovoltaic systems, preferably wherein the method comprises bonding between battery cells, cover sealing, cooling tube and / or channel bonding.
14. A method according to claim 13, wherein in step (ii), the printable structural adhesive composition provides an adhesive layer and / or a sealant, preferably wherein the adhesive layer and / or sealant forms at least a part of a sealant in a battery or fuel cell.
15. Use of a printable structural adhesive composition according to any one of claims 1 to 4 for joining and / or sealing parts in an industrial manufacturing operation.
16. Use of the printable structural adhesive composition according to any one of claims 1 to 4 for repairing holes in electrophoretically coated automobile bodies or parts thereof.
17. An electrophoretically coated automobile body or part thereof comprising holes covered by a substrate bonded to the electrophoretically coated automobile body or part thereof with a cured printable structural adhesive composition according to any one of claims 1 to 4.
18. A method for repairing a hole in an electrophoretic coated automobile body or a part thereof, the method comprising: (i) Holes in automobile bodies or parts thereof that are selected for electrophoretic coating; (ii) applying a substrate and a printable structural adhesive according to claims 1 to 4 such that the substrate covers the hole and the adhesive is disposed between the substrate and the surface of the electrophoretically coated automotive body or part thereof in proximity to the hole; as well as (iii) curing the adhesive.
19. The method of claim 18, wherein (ii) comprises applying the printable structural adhesive to: The substrate, and / or The surface of the electrophoretically coated automobile body or its parts at the location of the hole, or a combination thereof.
20. A method for repairing a hole (e.g., a hole in an electrophoretically coated automobile body or part thereof), the method comprising: (i) receiving data regarding the location of one or more holes of a second substrate (e.g., an automobile body or a component thereof); (ii) repairing the hole using a first substrate and an adhesive using the data.
21. The method of claim 20, wherein receiving the data comprises detecting one or more holes of the second substrate with an imaging system.
22. A method according to claims 20 to 21, wherein receiving the data comprises analysing a CAD drawing of the second substrate, such as a car body or a component thereof.
23. The method of claims 20 to 22, further comprising a user interface adapted to select one or more wells of an image provided by the imaging system or CAD drawing.
24. The method of claims 20 to 23, further comprising a user interface adapted to confirm a computer-generated selection of one or more apertures of an image provided by the imaging system or CAD drawing.
25. The method of claims 20 to 24, wherein (ii) comprises applying the adhesive with a robotic fluid dispenser to: the first substrate, and / or The surface of the second substrate (eg, an electrophoretically coated automobile body or part thereof) is located proximate to the hole.
26. A method according to claims 20 to 25, wherein (ii) includes contacting the first substrate with the second substrate (e.g., an electrophoretically coated automobile body or part thereof) using a robotic pick and place system so that the first substrate covers the hole and the adhesive is disposed between the first substrate and the second substrate at a position proximate to the hole.
27. A non-transitory computer readable medium storing one or more instructions that, when executed by a processor, cause the processor to: receiving data regarding the location of the apertures of a second substrate (e.g., an electrophoretically coated automobile body or component thereof); and The data is utilized to cover the hole with a first substrate and an adhesive disposed between the first substrate and the second substrate at a location proximate the hole.
28. The non-transitory computer readable medium storage of claim 27, further characterized by claims 21 to 25.
Citation Information
Patent Citations
Method and apparatus for seismic data processing by correlation
EP0249527A2
Method of forming a sealed edge joint between two metal panels
US6000118A
Sealed edge joint between two metal panels
US6368008B1
Structure of hemmed together metal plate materials
US6528176B1
Thermally curable precursor of a toughened thermo-expanded film and a film made thereof
WO2007014039A2